Rancang Bangun Generator Ozon Koaksial - Sulistianto, Agus Ernawan; Murdiya, Fri; Hamdani, Eddy (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
The developmentof science and technology, especially in industry, can have both positive` and negative effects.`One of the negative `effects is the higher pollution in soil, water and air. The use of ozone has now been widely applied in various fields, for example as a disinfectant for drinking water treatment, disinfecting germs, sterilizing medical devices and preserving food ingredients. Ozone can be generated by the dielectric barrier discharge method which is generally used as a method of generating ozone supplied with high voltage or also known as high voltage plasma generators. High voltage plasma occurs in the dielectric barrier discharge air gap due to the failure of air to maintain its insulating properties. The type of electrode used and the gap distance in the dielectric barrier dischrage test can affect the amount of plasma produced, and plasma also affects the yield of ozone concentration. In this research, a coaxial ozone generator will be designed with a variation of 3 inner electrodes, variations in the flow rate of oxygen input and the presence `or absence of the `influence of the magnetic field on` the ozone produced.Â  Â  Keywords: Science, Ozone, Dielectric Barrier Discharges, Electrodes, Plasma, Magnetic Field.